De novo biosynthesis of 8-hydroxyoctanoic acid via a medium-chain length specific fatty acid synthase and cytochrome P450 in Saccharomyces cerevisiae - Wernig, Florian; Boles, Eckhard; Oreb, Mislav (Metabolic engineering communications, 2020)
Terminally hydroxylated fatty acids or dicarboxylic acids are industrially relevant compounds with broad applications. Here, we present the proof of principle for the de novo biosynthesis of 8-hydroxyoctanoic acid from glucose and ethanol in the yeast Saccharomyces cerevisiae. Toxicity tests with medium-chain length ω-hydroxy fatty acids and dicarboxylic acids revealed little or no growth impairments on yeast cultures even at higher concentrations. The ability of various heterologous cytochrome P450 enzymes in combination with their cognate reductases for ω-hydroxylation of externally fed octanoic acid were compared. Finally, the most efficient P450 enzyme system was expressed in a yeast strain, whose fatty acid synthase was engineered for octanoic acid production, resulting in de novo biosynthesis of 8-hydroxyoctanoic acid up to 3 ​mg/l. Accumulation of octanoic acid revealed that cytochromes P450 activities were limiting 8-hydroxyoctanoic acid synthesis. The hydroxylation of both externally added and intracellularly produced octanoic acid was strongly dependent on the carbon source used, with ethanol being preferred. We further identified the availability of heme, a cofactor needed for P450 activity, as a limiting factor of 8-hydroxyoctanoic acid biosynthesis. •Low toxic effects of medium-chain ω-hydroxy fatty acids on yeast cells .•Systematic comparison of cytochrome P450 enzyme activities on octanoic acid .•De novo biosynthesis of 8-hydroxyoctanoic acid .•Improvement of cytochrome P450 activity with ethanol or by addition of hemin .